1980
DOI: 10.1128/jb.142.2.556-567.1980
|View full text |Cite
|
Sign up to set email alerts
|

Location of the multivalent control site for the ilvEDA operon of Escherichia coli

Abstract: A strain of Escherichia coli K-12 containing a deletion extending from early in the ilvE gene toward the ilvG gene was shown to exhibit a higher expression of the downstream genes, ilvD and ilvA, than did an ilv+ strain. The elevated expression was under apparently normal ilv-specific control, however. The deletion was transferred to the ilv region of Ah80dilv and shown by restriction endonuclease and heteroduplex analysis to extend through the deoxyribonucleic acid (DNA) shown, in the preceding paper (C. S. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…Previous studies from this laboratory had shown that ilv-specific control was exerted on the ilv genes in a plasmid carrying the entire ilv cluster (25). Phages that carried the lac genes fused to ilv DNA that extended through the ilvO region but not through the ilvG region did not exhibit ilv-specific control over 8i-galactosidase (9). However, if the ilvO region was deleted and ilv DNA extending beyond ilvG was included in the ilv-lac fusion phages, ilv-specific control over f8-galactosidase fornation was exhibited.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Previous studies from this laboratory had shown that ilv-specific control was exerted on the ilv genes in a plasmid carrying the entire ilv cluster (25). Phages that carried the lac genes fused to ilv DNA that extended through the ilvO region but not through the ilvG region did not exhibit ilv-specific control over 8i-galactosidase (9). However, if the ilvO region was deleted and ilv DNA extending beyond ilvG was included in the ilv-lac fusion phages, ilv-specific control over f8-galactosidase fornation was exhibited.…”
Section: Resultsmentioning
confidence: 89%
“…on July 14, 2020 by guest http://jb.asm.org/ Downloaded from REGULATION OF THE ilvGEDA OPERON 287 to the strong metabolic depression of synthesis of the isoleucineand valine-forming enzymes observed in strains with normal ilv regions (9). Thus, this metabolic depression is not a result of ilv-specific regulation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations